Vacuum sealing drainage combined with Traditional Chinese Medicine nursing appropriate techniques for a diabetic patient with back carbuncle (负压封闭引流联合中医护理适宜技术治疗1例糖尿病合并背部外痈的护理体会) - YANG Qingqing (杨青青); YAN Qiuyan (闫秋艳); LIU Fei (柳菲); LI Jie (李解); LIU Minghui (刘明慧) (中西医结合护理)
This article summarizes the experience of Traditional Chinese Medicine(TCM) nursing appropriate techniques for a diabetic patient with back carbuncle treated with vacuum sealing drainage (VSD) technology. Efforts have been made to enhance the continuous vacuum sealing drainage. Based on the TCM theory, nursing appropriate techniques such as auricular acupoint pressing, intradermal needling, TCM oral care, TCM five-tone therapy were carried out for management of blood pressure and diabetes mellitus, reduce the incidence the infection and improve the wound healing. (本文总结1例负压封闭引流技术(VSD)联合中医适宜护理操作技术治疗糖尿病合并背部外痈患者的护理经验。术前做好充分准备, 术后做好VSD持续引流的观察与护理。基于中医基础理论, 采用耳穴刺激、皮内针刺激、中药漱口液清洁口腔、中医五音疗法等中医护理适宜技术, 有效控制高血压、糖尿病等基础疾病, 降低感染风险, 促进创面的愈合。)